RNA Demethylase ALKBH5 Prevents Lung Cancer Progression by Regulating EMT and Stemness via Regulating p53 - Liu, Xiangli; Wang, Ziyi; Yang, Qiwei; Hu, Xiaohai; Fu, Qiang; Zhang, Xinyu; Li, Wenya (Frontiers in Oncology, 2022)
Background: Although N6-methyladenosine (m6A) RNA methylation is the most abundant reversible methylation of mRNA, which playing critical roles in regulating cancer processing, few studies have examined the role of m6A in Non small-cell Lung cancer derived cancer stem-like cells (CSCs). Methods: CSCs were enriched by culturing NSCLC cells in serum-free medium and stem factors, including CD24, CD44, ALDH1, Nanog, Oct4 and Sox2 were detected by western blot. ALKBH5 expression was measured by employing tissue array. Global m6A methylation was measured after ALKBH5 knockdown. Malignances of CSCs were detected by performing CCK-8 assay, invasion assay, cell cycle analysis and tumor formation in vitro and in vivo. Results: m6A demethylase ALKBH5 is highly expressed in CSCs derived from NSCLC. Knockdown of ALKBH5 increased global m6A level, and also increased E-cadherin, decreased stem hallmarkers, Nanog and Oct4, and inhibited stemness of CSCs. In lung carcinoma, it is found that ALKBH5 is positively correlated with p53 by using Gene Expression Profiling Interactive Analysis (GEPIA) online tool. P53 transcriptionally regulates ALKBH5, and subsequently regulates global m6A methylation level. Knockdown of p53 or inhibition of p53’s transcriptional activity by addition of its specific inhibitor PFT-α decreased expression of ALKBH5 and CSCs’ malignancies, including proliferation, invasion and tumor formation ability, indicates that p53 may partially regulates CSC’s malignancies via ALKBH5. Furthermore, we also found p53 transcriptionally regulates PRRX1, which is consistent with our previous report. Conclusion: Collectively, our findings indicate the pivotal role of ALKBH5 in CSCs derived from NSCLC and highlight the regulatory function of the p53/ALKBH5 axis in modulating CSCs progression, which could be a promising therapeutic targets for NSCLC.